Design Engine Decision Support System to Application Pharmaceuticals with Use Method Analytical Hierarchy Process - Adi Fitrianto; Carli Apriansyah; Donny; Dody (Jurnal Syntax Admiration, 2023)
This study aims to increase effectiveness in the selection of drug suppliers in the Tangerang public hospital pharmacy. Tangerang General Hospital is an agency engaged in the health and pharmaceutical services sector. This pharmaceutical division has an internal pharmaceutical application that has been implemented with various features used for recording transaction data both drug sales and drug purchases. Currently there is more than one supplier that supplies the same drug. Therefore the main focus of this research is to design an engine to feature a decision support system by utilizing the analytical hierarchy process approach for selecting the best specific medicine supplier. A decision support system (DSS) is an information system designed to assist decision makers in processing complex information and providing relevant data to support these decisions. The approach that used in this research is analytical hierarchy process with the criteria as needed. The conclusion of this research is to design a prototype engine that is able to provide information and recommendations about the best drug suppliers.